Uneasy self-promotion and tactics of patience: Finnish MPs' ambivalent feelings about personalised politics on social media - Mannevuo Mona (Sage Publications, 2022)
This article examines Finnish politicians' ambivalent attachments to social media - specifically Facebook and Twitter - in candidate-centred, personalised politics. The analysis draws on 20 semi-structured interviews with members of parliament (MPs) to investigate the tactics of adaptation and adjustment politicians develop in a work setting that precludes digital detox. To investigate the MPs' contradictory feelings, the analysis builds on cultural and media theory to contextualise the porous border between the personal and the political that exists on social media. The analysis revolves around four interconnected themes: uneasiness of self-promotion, Facebook's ordinariness, Twitter as a necessary evil, and tactics of patience MPs utilise when they encounter various forms of online harassment. The article suggests that in parliamentary research, social media should be considered an ambivalent social glue that holds things together rather than merely a platform for self-promotion.